Research advances in unilateral endoscopic spinal surgery for the treatment of lumbar disc herniation: a review - Nan Fang; Shilin Yan; Aofei Yang (Journal of Orthopaedic Surgery and Research)
Abstract Lumbar disc herniation is a common cause of back and leg pain. Treatment has evolved significantly from traditional open surgery towards minimally invasive spine surgery (MISS). Within MISS, unilateral endoscopic spinal surgery (UESS), such as percutaneous transforaminal endoscopic discectomy (PTED) and unilateral biportal endoscopy (UBE), has largely replaced older bilateral approaches. Recent innovations like one-hole split endoscopy (OSE) and arthroscopic-assisted uniportal surgery (AUSS) further expand UESS capabilities. This review provides the first comprehensive analysis of UESS evolution and its key surgical approaches. We systematically compare the technical features of major uniportal techniques, including established methods like TESSYS and interlaminar approaches, alongside newer developments such as the 45° puncture technique and Gu’s technique. Looking ahead, intelligent solutions and instrument innovation represent crucial future directions for UESS. Notably, this study formulates conceptual designs for a novel integrated non-coaxial spinal endoscope as potential future directions. These insights provide critical guidance for developing next-generation endoscopic devices in UESS.